Metagenomic sequencing of the bronchoalveolar lavage extracellular virome and cellular transcriptome of sarcoidosis patients does not detect rubella virus - Keeler, Emma L.; Vukmirovic, Milica; Yan, Xiting; Gulino, Kristin; Ghedin, Elodie; Kaminski, Naftali; Sullivan, Kathleen E.; Bushman, Frederic D.; Collman, Ronald G.; Rosenbach, Misha (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: Sarcoidosis is a multisystem granulomatous inflammatory disease of unclear etiology that involves the lung, skin and other organs, with an unknown antigenic trigger. Recently, evidence has been found in both immune deficient and immune competent patients for rubella virus in cutaneous granulomas. These granulomatous lesions share overlapping features with cutaneous sarcoidosis, raising the question of rubella virus in sarcoidosis. Objective: To investigate the presence of rubella virus in sarcoidosis lung samples. Methods: We employed metagenomic sequencing to interrogate extracellular virome preparations and cellular transcriptomes from bronchoalveolar lavage (BAL) of 209 sarcoidosis patients for rubella virus sequences. Results: We found no evidence for rubella virus genomes in acellular fluid or rubella virus gene expression in BAL cells of sarcoidosis patients. Conclusions: These findings argue against rubella virus infection or persistence within the lung at time of sampling as a sarcoidosis trigger.